Construction of Life Cycle Assessment Model of Carbon Emission in Hui Cultural Tourism Destination——Taking Huangshan City as an Example. (June 2020) - Mi, Xue; Zhao, Lei; Ding, Nan
Abstract: Tourists travel behaviours generate tourism waste, consume carbon energy, and emit carbon dioxide. To estimate and evaluate the carbon emissions and ecological environment of tourism destinations can provide data support for local tourism sustainable development programs. Considering the characteristics of the integration of Huangshan City's Hui culture and ecological environment, a life cycle assessment model of carbon emissions from Hui culture tourism destinations is established. According to the model, this paper proposes that increasing more activities in the scenic spot, managing carbon emission of enterprises related to scenic spot, and promoting the concept of green consumption.